2004
DOI: 10.1152/ajpheart.00314.2003
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated dilation in human brachial artery after different circulatory occlusion conditions

Abstract: Betik, Andrew C., Victoria B. Luckham, and Richard L. Hughson. Flow-mediated dilation in human brachial artery after different circulatory occlusion conditions. Am J Physiol Heart Circ Physiol 286: H442-H448, 2004. First published August 28, 2003 10.1152/ ajpheart.00314.2003.-Different magnitudes and durations of postocclusion reactive hyperemia were achieved by occluding different volumes of tissue with and without ischemic exercise to test the hypotheses that flow-mediated dilation (FMD) of the brachial art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 34 publications
10
113
0
3
Order By: Relevance
“…In a study evaluating the FMD in human brachial artery after different circulatory occlusion conditions revealed that the type of occlusion (proximal vs distal) had an effect on FMD. 28 These studies demonstrated that there are important betweenmethod differences in the FMD response of the brachial artery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study evaluating the FMD in human brachial artery after different circulatory occlusion conditions revealed that the type of occlusion (proximal vs distal) had an effect on FMD. 28 These studies demonstrated that there are important betweenmethod differences in the FMD response of the brachial artery.…”
Section: Discussionmentioning
confidence: 93%
“…However, some limitations on the measurement of blood flow in human brachial artery have been reported. 14,[26][27][28][29] The magnitude of FMD appears to be related to many factors in addition to artery studied, including the method of measurement (e.g. echo wall tracking vs echo Doppler imaging), site of occlusion (either proximal or distal to the measurement site), duration of occlusion and presence or absence of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Learoyd and Taylor 25 give wall thickness ratio h/r of about 0.15 at low pressures < 50 mmHg, so that the wall thickness would be 0.225 mm or 0.022 cm. Betik et al 26 found in control subjects using ultrasound at normal arterial pressures brachial artery radii averaging 0.22 cm. Iwamoto et al 27 , using ultrasound in adult human subjects with normal blood pressure found brachial artery radius averaging 0.2 cm and wall thickness 0.03 cm.…”
Section: Numerical Values Of Model Parametersmentioning
confidence: 99%
“…In addition, the subject squeezed a rubber ball in the left hand 20 times between the third and fourth minute of ischaemia in order to augment further post-occlusive hyperaemia. 17 After cuff deflation, velocity data were recorded at 10 and 120 seconds and frozen B-mode images in end-diastole at 45, 75, 105, 150 and 240 seconds. Following 10 minutes' rest, B-mode images were recorded before and five minutes after sublingual administration of 0.4 mg glyceryl trinitrate (GTN).…”
Section: B-mode Ultrasound Of Bamentioning
confidence: 99%